PENGARUH RETURN ON ASSETS (ROA), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS), TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018) - Nike Linnanda Dwi Putri; Nur Hajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to analyze the effect of Return On Assets, Net Profit Margins, and Earning Per Share on stock prices in manufacturing companies listed on the BEI in the 2014-2018 period. The independent variables used in this study are Return On Assets, Net Profit Margin, and Earning Per Share. While the dependent variable is the Stock Price. The sample in this study consisted of 19 manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period that were selected based on certain criteria using a purposive sampling method. The analysis used in this study is multiple linear regression analysis processed with SPSS. The results of the study using the t test concluded that partially the ROA and EPS variables had a significant positive effect on stock prices, while the NPM variable had a negative effect on stock prices.Keywords : Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS), and Stock Price